SCRUB TYPHUS INFECTION AMONG PUO CASES IN THE PEDIATRIC POPULATION IN A TERTIARY CARE HOSPITAL - A, ANUPRIYA; B, RAJKUMAR; N, PRABHUSARAN; BANTHAVI S, PRIYA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Scrub typhus is an acute, febrile, exanthematous illness. This disease is underdiagnosed in India due to its non-specific and varied clinical presentation, low index of suspicion among clinicians, and lack of diagnostic facilities. This study was carried out to know the seroprevalence of scrub typhus in children with PUO and to compare a rapid test with IgM enzyme-linked immunosorbent assay (ELISA) for the diagnosis of scrub typhus. Methods: This cross-sectional analytical study was conducted for a period of 1 year. The study population comprised mainly 280 young children attending pediatric OP and in patients admitted to a tertiary care teaching hospital with fever and related symptoms. The serum samples were tested for Weil-Felix reaction, IgM ELISA, and rapid card test. Results: The mean age group of the study population was 7–9 years, of which 20 cases were positive. The major predisposing factor for scrub typhus infection was vegetation around houses. The sensitivity and specificity of both, card test and IgM ELISA, were 100%. Conclusion: In this study, 7.1% of febrile children were positive for scrub typhus. Leptospirosis, dengue, and typhoid were the common coinfections found in scrub typhus, positive children. Early identification of cases and treatment at the earliest will prevent complications.